Dissociable effects of acute SSRI (escitalopram) on executive, learning and emotional functions in healthy humans. (December 2018) - Skandali, Nikolina; Rowe, James; Voon, Valerie; Deakin, Julia; Cardinal, Rudolf; Cormack, Francesca; Passamonti, Luca; Bevan-Jones, William; Regenthal, Ralf; Chamberlain, Samuel; Robbins, Trevor; Sahakian, Barbara
Abstract Serotonin is implicated in multiple executive functions including goal-directed learning, cognitive flexibility, response inhibition and emotional regulation. These functions are impaired in several psychiatric disorders, such as depression and obsessive–compulsive disorder. We tested the cognitive effects of the selective serotonin reuptake inhibitor escitalopram, using an acute and clinically relevant dose (20 mg), in 66 healthy male and female volunteers in a double-blind, placebo-controlled study. Participants performed a cognitive test battery including a probabilistic and reversal learning task, the CANTAB intra-dimensional/extra-dimensional shift test of cognitive flexibility, a response inhibition task with interleaved stop-signal and No-Go trials and tasks measuring emotional processing. We showed that acute escitalopram administration impaired learning and cognitive flexibility, but improved the ability to inhibit responses in stop-signal trials while leaving unaffected acute emotional processing. Our findings suggest a dissociation of effects of acute escitalopram on cognitive functions, possibly mediated by differential modulation of brain serotonin levels in distinct functional neural circuits.